2002
DOI: 10.17221/4851-pps
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes for resistanceto wheat powdery mildew in Hungarian, Polish and Slovak wheat cultivars

Abstract: AbstractŠVEC M., SZUNICS L., MIKLOVIČOVÁ M., SLOVÁKOVÁ T., TISOVÁ V., HAUPTVOGEL P. (2002): Identification of genes for resistance to wheat powdery mildew in Hungarian, Polish and Slovak wheat cultivars. Plant Protect. Sci., 38: 64-72.The objective of the study was to identify genes for resistance to powdery mildew in wheat cultivars and land races from Poland, Slovakia and Hungary. The presence and distribution of resistance genes was compared to powdery mildew virulence structure in these countries. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This species is an important object of research in many countries. Studies on resistance to powdery mildew in wheat have been conducted in Nordic countries (Hysing et al 2007), Slovakia (Bojnanska 2009), Czech Republic (Svec et al 2002;Vechet 2006), France (Zeller et al 1993), Lithuania (Liatukas & Ruzgas 2008, 2009), Brazil (Costamilan 2005), India (Ahmadi et al 2011), the USA (Niewoehner & Leath 1998;Parks et al 2008), Poland (Kowalczyk et al 1998), andTurkey (Spetsov et al 2013). Those studies mainly located resistance genes on chromosomes and identified molecular markers linked to those genes.…”
Section: Resultsmentioning
confidence: 99%
“…This species is an important object of research in many countries. Studies on resistance to powdery mildew in wheat have been conducted in Nordic countries (Hysing et al 2007), Slovakia (Bojnanska 2009), Czech Republic (Svec et al 2002;Vechet 2006), France (Zeller et al 1993), Lithuania (Liatukas & Ruzgas 2008, 2009), Brazil (Costamilan 2005), India (Ahmadi et al 2011), the USA (Niewoehner & Leath 1998;Parks et al 2008), Poland (Kowalczyk et al 1998), andTurkey (Spetsov et al 2013). Those studies mainly located resistance genes on chromosomes and identified molecular markers linked to those genes.…”
Section: Resultsmentioning
confidence: 99%
“…In Poland, the percentage of B. graminis f. sp. tritici isolates virulent to the Pm4a allele was high (>50%) already in the first years of the 21st century [42]. The absence of the marker for the Pm4a allele in the analyzed bread wheat cultivars suggests that this gene had been gradually withdrawn from breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings point to cyclic changes in the population of Bgt isolates. In the early years of the 21 st century, Bgt isolates in Poland were highly virulent to cultivars harboring the Pm4b allele [42]. However, the structure of Bgt isolates has not been researched extensively in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Pm2a , as a successfully cloned gene from Aegilops tauschii , is of great significance in wheat breeding for powdery mildew resistance. Švec et al [ 167 ] identified the Pm2 gene in 32 Polish wheat varieties. Agnieszka et al [ 168 ] identified seven wheat varieties from Europe by establishing a multiplex PCR reaction and found that all wheat varieties contained the Pm2 gene.…”
Section: Application Of Disease-resistant Genes From Aegilo...mentioning
confidence: 99%